Livelihood Petani dan Perhutanan Sosial: Analisis Karakteristik Sosial-Ekonomi untuk Pengelolaan Hutan Lestari - Astaman, Putra; Hikmah, Aulia Nurul; Dassir, Muhammad; Nadirah, Siti; Darwis, Muhammad (Agriculture and Socio-Economic Journal, 2025)
The Social Forestry Program is a community participation-based initiative for sustainable forest management, aimed at reducing poverty, protecting the environment, and improving farmers' welfare. This study aims to analyze the program's socio-economic impacts on farmer households in Enrekang District, South Sulawesi, focusing on 12 villages in 10 sub-districts. Mixed methods (quantitative and quantitative) were used through surveys, interviews, and observations of 372 respondents, including farmers, community leaders, and government representatives. Results show that participation in Social Forestry contributes to increased income, especially through superior commodities such as shallots and brown rice, as well as economic diversification such as dairy farming (dangke). However, challenges such as gender inequality (male dominant: 87.4%), limited market access, and climate change impacts still hinder the optimization of the program. Respondents' characteristics are dominated by productive age (40-61 years: 63.9%) with secondary education (SMA: 31.5%), while the average family size is 3-4 people (45.4%). The study highlights the importance of locally-based approaches, multi-stakeholder collaboration, and inclusive policies to strengthen program sustainability. The findings recommend strengthening farmers' capacity through training, increasing access to capital, and policy synergy to support sustainable livelihoods while maintaining forest ecosystems.